2016
DOI: 10.1037/cdp0000041
|View full text |Cite
|
Sign up to set email alerts
|

“They were just making jokes”: Ethnic/racial teasing and discrimination among adolescents.

Abstract: Objectives The effects of peer-based discrimination are especially harmful for adolescents given the heightened role of social feedback during this period. The current study aimed to understand the unique expressions of discrimination that adolescents experience between close peers and friends, as well as the daily influence of such experiences. Method Study 1 included semistructured interviews (10 interviews, 2 focus groups; Mage = 17.3) with an ethnic/racially diverse sample of adolescence. Study 2 (n = 79… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
88
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 110 publications
(103 citation statements)
references
References 84 publications
8
88
1
2
Order By: Relevance
“…In this context, what may be more relevant than children’s membership in a racial/ethnic group alone are personal experiences with differential treatment as a result of one’s group membership. It is notable that, with age, many adolescents, and particularly adolescents of African-American and Latino background, report increasing personal experiences with discrimination from teachers, peers, and strangers, with reports ranging from wrongful discipline in school to being hassled by store clerks to teasing and online harassment (Douglass, Mirpuri, English, & Yip, 2016; Fisher, Wallace, & Fenton, 2000; Rivas-Drake, Hughes, & Way, 2009; Umaña-Taylor, Tynes, Toomey, Williams, & Mitchell, 2015). Thus, it may be that, later in development (i.e., later in adolescence), increasing personal experiences with others’ biases would be associated with greater recognition of discriminatory resource allocation for racial/ethnic minority adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, what may be more relevant than children’s membership in a racial/ethnic group alone are personal experiences with differential treatment as a result of one’s group membership. It is notable that, with age, many adolescents, and particularly adolescents of African-American and Latino background, report increasing personal experiences with discrimination from teachers, peers, and strangers, with reports ranging from wrongful discipline in school to being hassled by store clerks to teasing and online harassment (Douglass, Mirpuri, English, & Yip, 2016; Fisher, Wallace, & Fenton, 2000; Rivas-Drake, Hughes, & Way, 2009; Umaña-Taylor, Tynes, Toomey, Williams, & Mitchell, 2015). Thus, it may be that, later in development (i.e., later in adolescence), increasing personal experiences with others’ biases would be associated with greater recognition of discriminatory resource allocation for racial/ethnic minority adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…For ethnic-racial identity salience, variability would mean that adolescents are at times very aware of their ethnic-racial identity, and at other times not at all aware of their ethnic-racial identity. For example, qualitative work highlights such experiences of stability and variability in adolescents’ own words (Douglass et al 2015 for study details). When asked by an interviewer “When you’re walking around and you’re going to classes and you’re hanging out with friends, are you aware of your race?” a 17-year old African American female responded:

Yeah I am, I don’t know…like it depends because sometimes when I’m in the cafeteria… I’m with certain groups right?

…”
Section: Introductionmentioning
confidence: 99%
“…Yet, as with teachers, peer discrimination can also be indirect. A recent daily diary study found that adolescents already experiencing anxiety who faced ethnic teasing from peers then reported heightened and prolonged anxiety (Douglass, Mirpuri, English, & Yip, 2016).…”
Section: Perceived Discrimination From Teachers and Peersmentioning
confidence: 99%